1995
DOI: 10.1002/hep.1840210221
|View full text |Cite
|
Sign up to set email alerts
|

Association of primary biliary cirrhosis with the allele HLA-DPB1*0301 in a German population

Abstract: The major histocompatibility complex class II alleles at the HLA-DPB1 locus were investigated in 32 German Caucasoid patients with primary biliary cirrhosis (PBC) and compared with those from 47 normal control patients using molecular genotyping techniques. The second exon of the HLA-DPB1 gene was amplified by polymerase chain reaction (PCR) and hybridized with 25 sequence-specific oligonucleotides (SSOs) to assign the HLA-DPB1 alleles on the basis of known sequence variations, according to the protocols of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1
3

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 46 publications
3
20
1
3
Order By: Relevance
“…HLA-DP associations have also been described in autoimmune diseases, such as CD (23), insulin-dependent diabetes mellitus (24), pauciarticular juvenile rheumatoid arthritis (25)(26)(27), and juvenile ankylosing spondylitis (28). In addition, an HLA-DP association has recently been demonstrated in primary biliary cirrhosis (29), in childhood common acute lymphoblastic leukemia (30), and also in Thai individuals with enhanced vaccine-induced Ab response to a malaria sporozoite Ag (31). However, some of these associations have not been confirmed (32,33), and in none of these examples has the association with HLA-DP been related to the restriction element used by T cells involved in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DP associations have also been described in autoimmune diseases, such as CD (23), insulin-dependent diabetes mellitus (24), pauciarticular juvenile rheumatoid arthritis (25)(26)(27), and juvenile ankylosing spondylitis (28). In addition, an HLA-DP association has recently been demonstrated in primary biliary cirrhosis (29), in childhood common acute lymphoblastic leukemia (30), and also in Thai individuals with enhanced vaccine-induced Ab response to a malaria sporozoite Ag (31). However, some of these associations have not been confirmed (32,33), and in none of these examples has the association with HLA-DP been related to the restriction element used by T cells involved in the disease.…”
Section: Discussionmentioning
confidence: 99%
“…36 It is possible that positive association might be 41 This association was not confirmed in several other studies from different non-British European populations. 32,35,36,42,43 Moreover, other European studies suggested significant associations of PBC with DR3 29,35 and DPB1*0301, 44 while the most recent study from the United States demonstrated an association between DRB1*08-DQA1*0401-DQB1*04 haplotype and PBC, albeit in a minority of patients. 40 Finally, studies from Japan failed to provide a consistent picture of HLA class II associations with PBC.…”
Section: Mhc and Pbcmentioning
confidence: 96%
“…However, it is to note that several European studies have failed to confirm an association with DRB1*08 (31, 52, 55, 57, 63). Other than DRB1*08 variant, it has been reported associations with DR3 (49, 55) or DPB1*0301 (64). In 2003, we suggested that the DRB1*11 allele has a protective effect against PBC in the Italian population (57).…”
Section: Hla Associations and Pbcmentioning
confidence: 99%